UNDERSTANDING THE CREATIVE TOURISM EXPERIENCE IN CULTURAL AND CREATIVE EVENTS/FESTIVALS - Carvalho, Rui (2020)
The specialised consumption of creative tourism experiences and their presence in cultural and creative events and festivals, constitute examples of reflexive tourism consumption. Following the line of research about the specialised consumption of creative tourism experiences and events, this research aims to describe and account for examples where cultural and creative events/festivals represent opportunities for participatory experiences like workshops. The author developed a systematic review using SCOPUS database, to account for creative tourism experiences present at cultural and creative events/festivals. Thirteen documents from 2003 to 2019, were chosen and analysed as they represent the confrontation between cultural and creative events/festivals and creative tourism experiences principles. Findings show that authors don´t always refer directly to creative tourism experiences in the events and festival case studies analysed. Results were organized under two perspectives the in creative tourism literature such "event/festival centred approach" discussed in as the creative city, creative spectacles and cultural and creative capital co-creation. Nonetheless, important creative contributions for the development of creative capital present at cultural and creative events and festivals are highlighted. The recent establishment of creative tourism as a research area and the small number of papers found constitute limitations to the study.